Prior Freezing Has Minimal Impact on the Contractile Properties of Permeabilized Human Myocardium - Gregory N. Milburn (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background Experiments measuring the contractile properties of human myocardium are important for translational research but complicated by the logistical difficulties of acquiring specimens. Accordingly, many groups perform contractile assays using samples that are acquired from patients at one institution and shipped to another institution for experiments. This necessitates freezing the samples and performing subsequent assays using chemically permeabilized preparations. It is unknown how prior freezing affects the contractile function of these preparations. Methods and Results To examine the effects of freezing we measured the contractile function of never‐frozen and previously frozen myocardial samples. Samples of left ventricular tissue were obtained from 7 patients who were having a ventricular assist device implanted. Half of each sample was chemically permeabilized and used immediately for contractile assays. The other half of the sample was snap frozen in liquid nitrogen and maintained at –180 °C for at least 6 months before being thawed and tested in a second series of experiments. Maximum isometric force measured in pCa 4.5 solution, passive force measured in pCa 9.0 solution, and Hill coefficients were not influenced by prior freezing (P=0.07, P=0.14, and P=0.27 respectively). pCa50 in never‐frozen samples (6.11±0.04) was statistically greater (P<0.001) than that measured after prior freezing (5.99±0.04) but the magnitude of the effect was only ≈0.1 pCa units. Conclusions We conclude that prior freezing has minimal impact on the contractile properties that can be measured using chemically permeabilized human myocardium.